Sporotrichosis from a tertiary care hospital in the Eastern State of India - Sharma, Loknandini; Agarwal, Reetu; Nachiketa, Nachiketa (Indian Journal of Case Reports, 2024)
Sporotrichosis is a form of subcutaneous or systemic fungal infection caused by Sporothrix schenkii. This is a thermophilic, dimorphic fungus that occurs worldwide in tropical and temperate areas. We report a case series of sporotrichosis in three patients from a tertiary care center in Assam. The source of infection could be identified in each patient. The patients were successfully treated with oral and topical antifungal agents, which included capsule Itraconazole and supersaturated potassium iodide therapy.